The carrot genome provides insights into crop origins and a foundation for future crop improvement - Simon, Phillip (2016)
Vavilov (1951) placed the center of origin of cultivated carrot in Central Asia, and an analysis of molecular diversity in wild and cultivated carrots from around the world demonstrated that wild carrots from Central Asia were more similar to cultivated carrots (Iorizzo et al., 2013), confirming Vavilov’s conclusions. Carrots may have been cultivated as a root crop in the Roman Empire, with extensive cultivation first recorded around 900 AD in Central Asia – Afghanistan in particular (Stolarczyk and Janick, 2011; Banga, 1963). Color has played an important role in the history of carrot domestication. The first Central Asian carrots were yellow or purple, and in the early 1500s, orange carrots were noted in still life paintings and some written accounts in Europe. Central Asian carrots spread first to the west beginning in the 900s, through the Middle East, North Africa, and then Europe; and to the east to South and North Asia (Banga, 1963). Orange carrots are grown globally today but yellow, purple, red, and white carrot land races, and some modern cultivars, are grown on a more limited scale in several parts of the world.